Respuestas
Respuesta dada por:
2
Respuesta:
1) x + 6 = 10 + 2
x = 12 - 6
x = 6
2) 7x + 13 = 4x + 28
7x =4x + 28 - 13
7x = 4x + 15
7x - 4x = 15
3x= 15
x = 5
5) x + 5 + 3x + 7 = 2x + 18
x + 3x + 5 + 7 =2x + 18
4x + 12 = 2x + 18
4x = 2x + 18 - 12
4x = 2x + 6
4x - 2x = 6
2x = 6
x = 3
6) (x + 5)/3 = 10
(x + 5 ) = 10 * 3
x + 5 = 30
x = 30 - 5
x = 25
Explicación paso a paso: espero que te ayude
gustavocarhuas1:
bjea
Preguntas similares
hace 4 años
hace 4 años
hace 7 años
hace 7 años
hace 7 años
hace 8 años